Pengaruh Leverage, Kepemilikan Keluarga, kepemilikan asing terhadap Manajemen Laba pada Sektor Makanan dan Minuman yang Terdaftar di BEI tahun 2016-2019 - Sugesti, Leli; Anindya, Desy Astrid; Rahman, Fauziah (Jurnal Akuntansi Nommensen, 2023)
This study aims to examine the effect of Leverage, Foreign Ownership and Family Ownership together and partially on Earnings Management. The population in this study were all Food and Beverage Companies listed on the Indonesia Stock Exchange (IDX) for the period 2016-2019. Which amounted to 26 companies. The statistical processing method uses Multiple Linear Analysis. The results showed that Leverage, Foreign Ownership and Family Ownership together had an effect on Earnings Management. Simultaneous test results Leverage has a negative effect on earnings management, Foreign Ownership has no effect on earnings management and Family Ownership has a negative effect on Earnings Management in the Food and Beverage Subsector listed on the IDX for the 2016-2019 period.